ANÁLISIS DE LA OFERTA TURÍSTICA AGROPECUARIA EN LOS RÍOS - GARCES AGUIRRE ROMEL JAYR (2024)
The study analyzes the agricultural supply in southern Los Ríos province, focusing on Baba, Babahoyo and Montalvo. The study identifies 15 farms with agritourism potential, although data collection in Babahoyo and part of the Baba and Montalvo farms is limited due to access restrictions. Interviews show that demand is focused on educational and recreational experiences in nature, with Hacienda Los Prados standing out for its infrastructure and popularity. Opportunities and challenges for agrotourism development were identified, suggesting a diversified and integrated offer to better satisfy demand. Surveys conducted in Baba and Montalvo complemented the data obtained.